Community happiness index for sustainable development in Putrajaya, Malaysia - Danladi, Musa Haruna (2017)
Urbanisation in Malaysia has led to significant pressure on local and state governments to provide planning and urban development strategies that are intended to improve the quality of urban services in ensuring citizens’ well-being or happiness. Cities are facing increasing complex issues and rapid changes that challenge their future direction. The problems in cities have highlighted the need for policy makers to foster well-being as an essential element of sustainable development. Thus, creating healthy and viable communities aim to provide high quality of life has become a focus of contemporary public policies that target city communities across the nation, especially in a new town development including Putrajaya. However, the mainstream sustainable community development frameworks neglect to make happiness a goal. The general objective of this study therefore, is to develop a community happiness index (CH-index) framework to measure resident’s satisfaction based on sustainable development indicators in Putrajaya city, from subjective well-being context. The study utilised mixed method approach with triangulation design in the development of this framework to achieve the primary research aim and specific objectives. Two sources of data sets were collected and used in this research analysis. Combined qualitative and quantitative data were collected from a two-round Delphi survey from a purposively sampled panel of experts in the sustainable development field in Malaysia, and the quantitative data gathered from the public survey of residents. The Delphi expert’s panel identified and selected relevant indicators, assigned weights to indicators, dimensions and domains attribute required to develop community wellbeing framework that facilitate urban policy initiatives. Consensuses were reached on 37 key indicators within four-sustainability dimensions with a high level of group agreement (Kendall’s W= 0.485, p < 0.001), and high correlation in rounds rankings (rho = 0.945, p < 0.01). Before application to the case study, the framework was tested to validate the psychometric property using Partial Least Square Structural Equation Modelling (PLS-SEM) to establish its robustness in measuring community happiness. Linear Additive aggregation model was used with the weightings to construct composite indices that consider the unique characteristics of communities and municipalities in Malaysia. Following a cross-sectional survey using the newly constructed composite framework to measuring level of community happiness in Putrajaya, we found out that the municipality has medium-high level of community happiness (6.866) on a 10-point response scale at almost sustainable level. The framework provide provides a mechanism for continuous monitoring and assessment of sustainable interventions, facilitate comparison of trends of sustainability over time and guide urban planning and policy making decisions process to evaluate progress and impact to promote appropriately efficient happiness and further sustainability.